A sinister splendor - Blakely, Mike (Forge, 2019)
Pairing extensive research with a brilliance for reviving the past in gripping narrative, Spur Award-winning author Mike Blakely has penned an epic novelization of the Mexican-American War in A Sinister Splendor. It's 1845. Texas joins the union and Mexico threatens war over the disputed Texas border. Meanwhile, expansionists dream of an America that sprawls all the way to the Pacific Coast. Can a conflict with an already war-torn Mexico satisfy this lust for territory? The Mexican-American War becomes the heroic proving ground for future Civil War generals and presidents of the United States, Mexico, and the Confederacy. But the glories of victory are tempered by the horrors of war--lives lost, bodies battered, souls shattered, dreams crushed, whole cities razed, and innocence forever dashed.